Measurement of the inclusive jet cross section in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We report on a measurement of the inclusive jet cross section in pp̄ collisions at a center-of-mass energy s=1.96TeV using data collected by the D0 experiment at the Fermilab Tevatron Collider corresponding to an integrated luminosity of 0.70fb-1. The data cover jet transverse momenta from 50 to 600 GeV and jet rapidities in the range -2.4 to 2.4. Detailed studies of correlations between systematic uncertainties in transverse momentum and rapidity are presented, and the cross section measurements are found to be in good agreement with next-to-leading order QCD calculations. © 2008 The American Physical Society.
Keywords: Jets; Tellurium compounds; A-center; Cross sectioning; Cross-section measurements; Data cover; Fermilab Tevatron Collider; Integrated luminosity; Next-to-leading order; QCD calculations; Systematic uncertainties; Transverse momentum; Uncertainty analysis